An assumption network-based approach to support margin allocation and management - El Fassi, Soufiane; Guenov, Marin D.; Riaz, Atif (Cambridge University Press, 2020)
Presented is an approach to support margin allocation and management via a graph-theoretical network of assumptions. In contrast to the document-centric approach, the network captures assumptions dependencies, and enables an algorithmic process supporting margin allocation and management. Ultimately, this methodology is intended to assist decision-makers in managing assumptions and examining their impact on an architecture. Explicitly linking margins to assumptions allows to support mitigating their risk of invalidity. The approach is demonstrated with a conceptual aircraft design example
Keywords: margin; assumption management; uncertainty; decision making; conceptual design